2018
DOI: 10.1111/1365-2435.13135
|View full text |Cite
|
Sign up to set email alerts
|

Trait selection and community weighting are key to understanding ecosystem responses to changing precipitation regimes

Abstract: Plant traits can be used to predict ecosystem responses to environmental change using a response–effect trait framework. To do this, appropriate traits must be identified that explain a species' influence on ecosystem function (“effect traits”) and the response of those species to environmental change (“response traits”). Response traits are often identified and measured along gradients in plant resources, such as water availability; however, precipitation explains very little variation in most plant traits gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(114 citation statements)
references
References 78 publications
4
110
0
Order By: Relevance
“…Under dry conditions, plants are expected to decrease their leaf surface and SLA to prevent the evaporation of water and thus enhance the water‐use efficiency. However, these leaf traits have also been shown to be highly species‐specific (Griffin‐Nolan et al., ) which impedes the prediction of general drought responses. Flower number decreased significantly with lower precipitation in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Under dry conditions, plants are expected to decrease their leaf surface and SLA to prevent the evaporation of water and thus enhance the water‐use efficiency. However, these leaf traits have also been shown to be highly species‐specific (Griffin‐Nolan et al., ) which impedes the prediction of general drought responses. Flower number decreased significantly with lower precipitation in our experiment.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that dry-adapted microbial species may be buffering plants from water and nutrient limitations (Vurukonda et al 2016a), and thereby reducing the demand for increasing leaf construction costs (LDMC) or belowground biomass allocation (root-to-shoot ratio). Recent work has highlighted the importance of identifying appropriate response traits to climatic variables such as precipitation (O'Brien et al 2017b, Griffin-Nolan et al 2018. Our results suggest that leaf and allocation traits measured here are less useful for assessing trait shifts in this semiarid system than physiological traits such as nonstructural carbohydrate concentrations or hydraulic conductance.…”
Section: Traitsmentioning
confidence: 75%
“…In addition, functional traits may be good metrics to gauge population responses to climatic variables (O'Brien et al 2017b, Griffin-Nolan et al 2018. For example, leaf dry matter content (LDMC), which is associated with photosynthetic capacity, relative growth rate and leaf longevity (Cornelissen et al 2003), is regulated by construction costs related to plant water status.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding strategies of water use and acquisition, often termed hydraulic strategies, and the functional traits that define them is critical to understanding the roles different types and species of vegetation play in the carbon and water cycles, predicting vegetation responses to climate change, and predicting the impacts of drought, disturbances, and other extreme events on the land surface [18]. To that end, Griffin-Nolan, et al [19] demonstrated that hydraulic traits can be used to predict ecosystem-level responses to changing precipitation patterns. In the context of our changing climate, vegetation regulated feedbacks between the biosphere and atmosphere are expected to change with changing temperature and precipitation [20][21][22][23][24].…”
Section: Functional Trait Covariationmentioning
confidence: 99%